2021
DOI: 10.5194/hess-25-1943-2021
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of human intervention – or not? Downstream intensification of hydrological drought along a large Central Asian river: the individual roles of climate variability and land use change

Abstract: Abstract. The transboundary Helmand River basin (HRB) is the main drainage system for large parts of Afghanistan and the Sistan region of Iran. Due to the reliance of this arid region on water from the Helmand River, a better understanding of hydrological-drought pattern and the underlying drivers in the region is critically required for effective management of the available water. The objective of this paper is therefore to analyze and quantify spatiotemporal pattern of drought and the underlying processes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 95 publications
1
21
0
Order By: Relevance
“…In summary, accusations of dishonesty and a lack of accountability have been widely made by authorities and officials from both parties, especially during the past 26 official meetings of the commisioners, ,,,, as well as by scholars from both countries. ,− ,, We, however, argue that honesty and accountability, which are the first stages in developing trust between the riparian nations of a shared watercourse, could be achieved in the Helmand River Basin if both countries complied with the existing treaty by specifying the three points of water delivery at the political border of Afghanistan and Iran, as well as by weatherizing and upgrading the monitoring technology at the Dehrawud Station.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, accusations of dishonesty and a lack of accountability have been widely made by authorities and officials from both parties, especially during the past 26 official meetings of the commisioners, ,,,, as well as by scholars from both countries. ,− ,, We, however, argue that honesty and accountability, which are the first stages in developing trust between the riparian nations of a shared watercourse, could be achieved in the Helmand River Basin if both countries complied with the existing treaty by specifying the three points of water delivery at the political border of Afghanistan and Iran, as well as by weatherizing and upgrading the monitoring technology at the Dehrawud Station.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the Iranian government demanded their rightful share of water from the Helmand River, especially during periods of drought, Afghan authorities claimed that the flow of the Helmand had declined due to climatic changes. 37 According to Nagheeby, 125 46 the commissioners of both riparian countries are accountable for specifying the three water delivery points near the Afghan−Iran political border after the treaty entered into force. 46 These water delivery points are (1) "at the place where the boundary line crosses the rude Seistan" and (2) "at two other places where the boundary line is located in the bed of the Helmand River between boundary pillars numbers 51 and 52" (also called markers 51 and 52) 43 (Article IIIa, pp 1−2).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that catchment topography, precipitation and geology (in decreasing order) were the most important environmental characteristics governing the severity of ELFs. Similarly, Roodari et al (2021) reported that the downstream intensification of ELFs along the Helmand River, Afghanistan, was largely attributable to precipitation deficits, while flow regulation and irrigation abstraction practices yielded limited effects. Such large-scale studies are challenging to undertake as they require extensive data collation, quality assurance, and analysis of environmental information from multiple data sources (e.g.…”
Section: The Spatial Variability Of Elfsmentioning
confidence: 97%
“…The model is based on hydrological response units (HRUs), as utilized and described, for example, by Gao et al (2014) and Prenner et al (2018). The aim is to represent dominant physical processes in the catchment based on topography and land cover classes while limiting model complexity (Savenije, 2010). A detailed model description is given in Sect.…”
Section: Model Structurementioning
confidence: 99%